Calsequestrin 2 deletion causes sinoatrial node dysfunction and atrial arrhythmias associated with altered sarcoplasmic reticulum calcium cycling and degenerative fibrosis within the mouse atrial pacemaker complex(1) - Glukhov, Alexey V. (Eur Heart J, 2015)
AIMS: Loss-of-function mutations in Calsequestrin 2 (CASQ2) are associated with catecholaminergic polymorphic ventricular tachycardia (CPVT). CPVT patients also exhibit bradycardia and atrial arrhythmias for which the underlying mechanism remains unknown. We aimed to study the sinoatrial node (SAN) dysfunction due to loss of CASQ2. METHODS AND RESULTS: In vivo electrocardiogram (ECG) monitoring, in vitro high-resolution optical mapping, confocal imaging of intracellular Ca(2+) cycling, and 3D atrial immunohistology were performed in wild-type (WT) and Casq2 null (Casq2(−/−)) mice. Casq2(−/−) mice exhibited bradycardia, SAN conduction abnormalities, and beat-to-beat heart rate variability due to enhanced atrial ectopic activity both at baseline and with autonomic stimulation. Loss of CASQ2 increased fibrosis within the pacemaker complex, depressed primary SAN activity, and conduction, but enhanced atrial ectopic activity and atrial fibrillation (AF) associated with macro- and micro-reentry during autonomic stimulation. In SAN myocytes, CASQ2 deficiency induced perturbations in intracellular Ca(2+) cycling, including abnormal Ca(2+) release, periods of significantly elevated diastolic Ca(2+) levels leading to pauses and unstable pacemaker rate. Importantly, Ca(2+) cycling dysfunction occurred not only at the SAN cellular level but was also globally manifested as an increased delay between action potential (AP) and Ca(2+) transient upstrokes throughout the atrial pacemaker complex. CONCLUSIONS: Loss of CASQ2 causes abnormal sarcoplasmic reticulum Ca(2+) release and selective interstitial fibrosis in the atrial pacemaker complex, which disrupt SAN pacemaking but enhance latent pacemaker activity, create conduction abnormalities and increase susceptibility to AF. These functional and extensive structural alterations could contribute to SAN dysfunction as well as AF in CPVT patients.